Threshold results of blow-up solutions to Kirchhoff equations with variable sources - TOUIL, Nadji; RAHMOUNE, Abita (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
This paper analyzes an initial boundary value problem for variable source Kirchhoff-type parabolic equations. We aim to derive a new sub-critical energy threshold for finite-time blow-up, a new blow-up condition, and estimates for lifespan and upper bounds for blow-up time across various initial energy cases. Mathematics Subject Classification (2010): 35B40, 35B44, 35K55 Received 17 February 2025; Accepted 01 June 2025.